The reference genome sequence of the scarlet follicle, Sterculia lanceolata, reveals a paleo-polyploidization and its impact on fruit quality and fruit dehiscence - Youtao Hu; Youpeng Zhang; Hongbin Zhang; Jiahao Zhang; Guilian Guo; Kejing Yang; Bing-Yan Shao; Jia-Yu Xue; Robert Henry; Wenquan Wang; Fei Chen (Functional & Integrative Genomics, 2026)
Sterculia lanceolata , a tree species of the Malvaceae family with notable ornamental and medicinal value, has long been constrained in genetic research and breeding applications due to the lack of genomic resources. In this study, we report for the first time a high-quality, chromosome-level genome assembly of this species, aimed at elucidating its evolutionary history and the genetic basis of key traits. We constructed the genome using PacBio HiFi sequencing and further assembled it into 20 pseudochromosomes with the aid of Hi-C technology, yielding a final genome assembly size of 602.8 Mb with a contig N50 of 29.3 Mb and a BUSCO completeness of 98.7%. The assembly includes the identification of 20 pseudochromosomes and the annotation of 35,873 protein-coding genes, with an annotation rate of 96.4%. By integrating genomic data from other Malvaceae species, we analyzed the karyotype evolution of S. lanceolata and revealed the basal ploidy level of the family. Comparative genomic analyses uncovered significant syntenic relationships and whole-genome duplication (WGD) events among Malvaceae species, thereby clarifying the trajectory of karyotype evolution. Moreover, the study identified key regulatory gene families associated with fruit dehiscence (homologs of SHP1/2 , FUL , IND , and ALC ) that have undergone extensive expansion in S. lanceolata as a consequence of ancient polyploidy events. The reference genome provided in this study not only serves as a critical resource for evolutionary research in Malvaceae but also establishes a foundational framework for molecular breeding, genetic improvement, and conservation of S. lanceolata and related species.

Asynchronous variation between aboveground carbon storage and structural complexity motivates stage-specific structural regulation across successional stages in Pinus kesiya var. langbianensis secondary forests - Zhi Liu; Hongbin Luo; Yong Wu; Shiqi Su; Yuansu Xu; Jing Li; Zhibo Yu; Lei Bao; Zongjian Peng; Hao Zhou; Xiaohan Liu; Weibin Wang; et al. (Forest Ecology and Management, 2026)

Novel multimodal data fusion strategies for nondestructive real-time monitoring of guava quality during storage - Jingxiao Yu; Zongxin Liu; Hongbin Pu; Da-Wen Sun (Postharvest Biology and Technology, 2026)

Fe-Co/sodalite derived from coal gangue via in-situ Fe utilization for synergistic peroxymonosulfate activation: Degradation of sulfamethoxazole, pathway elucidation, and toxicity attenuation - Yiwen Li; Huangsiyu Zhao; Jiang Yu; Pengxinyue Huang; Ming Chen; Yinying Jiang; Jingyi Xiong; Jinchao Huang; Hongbin Jiang (Journal of Water Process Engineering, 2026)

Simultaneous antibiotic degradation and water disinfection over a corrugated-plate TiO2/WO3 Z-Scheme photocatalytic reactor enabled by a Ti-O-W electron bridge - Zhengxuan Li; Yumeng Yang; Yimai Zhang; Xiaohui Zhang; Hongbin Yu; Yahui Zhao; Ying Lu (Journal of Environmental Chemical Engineering, 2026)

Identification and taste characteristics of novel salt taste-enhancing peptides from defatted Antarctic krill (Euphausia superba) powder hydrolysate and their molecular mechanisms of interaction with the TMC4 channel - Hongbin Chen; Peisheng Chen; Wenzhu Li; David Kwizera; Jean Maurice; Tingting Hou; Zhongjie Yu; Di Sun; Yu Liu; Xiaojun Yan; Shuoqi Jiang; Qingbao Ma; et al. (Food Research International, 2026)

Metal–insulator–metal metamaterial assisted signal enhanced spectroscopy for sugar concentration prediction in a simulated juice matrix - Jingxiao Yu; Da-Wen Sun; Zongxin Liu; Hongbin Pu (Food Chemistry, 2026)

Bioinspired rose-petal-like SnS₂ semiconductor with sulphur vacancies for highly sensitive SERS detection of acetamiprid in vegetables and fruits - Xinru Yu; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2026)

Optimized semi-chemical pulping of Arundo donax L. biomass: Correlating chemo-mechanical pretreatment with fiber morphology and paper strength - Peng Yu; Liqin Liu; Xiaofeng Lyu; Yinying Long; Shaodong Song; Jianhua Zhao; Bin Lu; Qingliang Xu; Zhengbai Cheng; Hongbin Liu; Xingye An (Biomass and Bioenergy, 2026)

Unraveling the adsorption mechanism of PFAS on biochar: A cross-scale integration of DFT calculations and interpretable machine learning - Xiang Guo; Gongmao Wang; Kefei Zhang; Yu Zhang; Jian Yang; Hongbin Gao; Xiaoxian Hu; Junfeng Wu; Kai Jiang; Dapeng Wu; Yanli Mao (Chemical Engineering Journal, 2026)

Enhanced soil organic carbon sequestration due to long term straw incorporation in Northeast China's paddy soils: Insights from soil profile fertility and aggregate stability - Yanmei Dong; Yong Jing; Ying Liu; Haoxin Zhang; Shengyue Yu; Owen Fenton; Wenxuan Shi; Xinzhong Du; Miaoying An; Bingqian Fan; Hongbin Liu (Journal of Environmental Management, 2026)

Stable and reliable method for simultaneous quantification of five neonicotinoid residues in plant-derived foods - Xinru Yu; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2026)

System-level metabolic and enzyme engineering enables high-titer gastrodin biosynthesis in yeast - Xiaowen Wan; Donghao Li; Minghai Tang; Zewen Liu; Jiayu Pan; Hongbin Yu; Jinliang Yang; Huayi Liu (Bioresource Technology, 2026)

Coupled impacts of river plume and upwelling on biogeochemistry in the Pearl River Estuary - Yanmin Wang; Jin-Yu Terence Yang; Lifang Wang; Tao Huang; Zhe Wang; Hongbin Liu; Jianping Gan; Tom Jilbert; Minhan Dai (Science China Earth Sciences, 2026)

Visual Perception and Gamma Oscillations in Cat V1 are Dynamically Correlated in Contrast Sensitivity Functions - Zheng Ye; Jian Ding; Changning Cheng; Hao Yu; Fei Xu; Qingyan Sun; Hongbin Yang; Tianmiao Hua; Hao Wang (Neuroscience Bulletin, 2026)

SEC10 suppresses KLF15-mediated transcriptional activation of JAK1 and promotes BoHV-1 replication - Wenqing Ma; Xiao Yu; Yanan Xu; Fachao Sun; Mengrui Zhao; Xinlei Wang; Yanjun Huan; Xin Yin; Hongmei Wang; Hongbin He (Veterinary Microbiology, 2026)

Metabolomics analysis reveals dynamic changes in the quality components and antioxidant activity capacity during variable temperature drying of Jinsihuangju (Chrysanthemum morifolium) tea - Yuanyuan Sun; Caixia Gao; Chunli Wang; Wenxuan Zhou; Xinyue Jia; Hongbin Yang; Youben Yu; Weidong Wang; Yuying Qi (Food Research International, 2026)

Nanoconfined bimetallic functionalized ceramic membrane with O3 micro-nano-bubbles for synergistic treatment of highly-salinity wastewater - Mingzhu Ren; Xinmin Zhai; Shuang Wang; Jiakai Qiu; Fenghao Yu; Yu Cui; Hongbin Cao; Yongbing Xie (Water Research, 2026)

Direct upcycling of Mn-rich residues into γ-MnOOH for efficient Alkaline OER - Wenting Jia; Lin Guo; Zhao Yu; Zhiqiang Li; Pengge Ning; Hongbin Cao (Journal of Environmental Management, 2026)

Advancing airborne pollen mapping with integrated ground and satellite observations - Yingxiao Zhang; Yi Liu; Kai Zhu; Hongbin Yu; Qian Tan; Allison L. Steiner (Remote Sensing of Environment, 2026)

Factors affecting spatial variability in organic carbon storage and sources in an intertidal Halophila beccarii seagrass meadow of the Yifengxi Estuary, Southern China - Xiaomei Shen; Yiguo Hong; Fei Ye; Jiapeng Wu; Yu Wang; Fen Guo; Hang Wan; Hongbin Liu (Marine Environmental Research, 2026)

Effect of protein–polyphenol interactions on the structural and digestive properties of pork myofibrillar proteins - Yu Chen; Qingyao Jiang; Yan Lu; Qiao Zeng; Ping Liu; Jiaxin Chen; Hongbin Lin; Jie Tang; Jie Zhao (Journal of Food Engineering, 2026)

Multi-omics reveals efficient thiamethoxam biodegradation but altered flavor profile by native microbiota during Pixian broad bean paste fermentation - Xuan Yu; Siqi Huang; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (International Journal of Food Microbiology, 2026)

Enhanced photocatalytic degradation of ciprofloxacin by modulating charge carrier transfer at the heterointerface of cyano-modified carbon nitride/boron nitride - Ruojia Ji; Yunhe Gong; Hongbin Yu; Xinhong Wang; Weichao Qin (Chemical Engineering Journal, 2026)

Environmental drivers and key taxa shaping diatom–dinoflagellate ratios in eutrophic coastal waters - Lingshuai Zhang; Zhiqin Wang; Jin-Yu Terence Yang; Shuqun Song; Zhaozhang Chen; Kuanbo Zhou; Hao Zhang; Yehui Tan; Hongbin Liu; Dazhi Wang; Xiaomin Xia (Marine Life Science & Technology, 2026)
Diatoms and dinoflagellates are two pivotal phytoplankton groups present in coastal ecosystems that play key roles in marine food webs and biogeochemical cycles. The diatom-to-dinoflagellate ratio (diat/dino ratio) serves as an indicator of ecosystem status and phytoplankton community dynamics; however, the specific taxa that contribute to its variability remain poorly understood. This study investigated the phytoplankton community composition and diat/dino ratios in the coastal regions of the East China Sea and northern South China Sea during summer using quantitative PCR (qPCR) and 18S rRNA gene pyrosequencing. The qPCR results revealed that diatoms dominated in the estuarine and nearshore waters, whereas dinoflagellates prevailed in the offshore regions. Random Forest analysis identified dissolved oxygen (DO) and the nitrogen-to-phosphorus (N:P) and silicon-to-nitrogen (Si:N) ratios as the primary drivers of variation in the diat/dino ratio. The influence of N:P ratios was further modulated by the absolute nitrogen and phosphorus concentrations. Taxonomic profiling revealed that Thalassiosiraceae and Chaetocerotaceae were enriched in nutrient-rich estuarine waters, while Leptocylindraceae, Bacillariaceae, and Skeletonemaceae dominated in regions with low N:P ratios. In contrast, dinoflagellate families, such as Thoracosphaeraceae, Pyrocystaceae, Peridiniaceae, and Heterocapsaceae, were more abundant in environments with high DO and elevated N:P ratios. Notably, the northward expansion of Scrippsiella (Thoracosphaeraceae) drove changes in the bloom dynamics that threaten the coastal ecosystem balance. These findings demonstrate that nutrient stoichiometry and oxygen availability influence the diat/dino ratio by favoring distinct phytoplankton taxa, thus offering insights into how anthropogenic nutrient inputs shape community structure and guide coastal ecosystem management.

Corrigendum to “Elimination of copper obstacle factor in anaerobic digestion effluent for value-added utilization: Performance and resistance mechanisms of indigenous bacterial consortium” [Water Research 252 (2024) 121217] - Zhiqiang Gu; Hongbin Yan; Qi Zhang; Yunpu Wang; Cuixia Liu; Xian Cui; Yuhuan Liu; Zhigang Yu; Xiaodan Wu; Roger Ruan (Water Research, 2026)

Deep eutectic solvents-synergistic ultrasonic-assisted extraction of polyphenols from flaxseed (Linum usitatissimum L.) meal: Optimization, mechanisms, in vitro activity, and structural characterization - Zhanglian Chen; Shiyong Li; Zhilin Zhou; Jiaqi Zhao; Yuxin Fu; Xiaoman Qin; E-yu Ma; Xinyi Jiang; Wenyu Liu; Hongbin Wu; Yi Xu; Changqing Wei (Food Research International, 2026)

A novel retrieval of global dust optical depth and effective diameter based on MODIS thermal infrared observations - Jianyu Zheng; Hongbin Yu; Yaping Zhou; Yingxi Shi; Zhibo Zhang; Claudia Di Biagio; Paola Formenti; Alexander Smirnov (Remote Sensing of Environment, 2026)

Response of macrobenthic diversity and functional traits to eutrophication pressures: Insights from three subtropical estuaries - Jian-Yu Dong; Weihao Liu; Hongbin Zeng; Xiaolong Yang; Xin Sun; Gorka Bidegain; Xuefeng Wang (Marine Environmental Research, 2026)

Radical-Net: A chemistry-enhanced transformer for elementary radical reactions in pollutant chemistry - Zhi Huang; Jiang Yu; Wei He; Pengxinyue Huang; Siwei Deng; Hongbin Jiang; Jie Yu; Chun Yang; Cheng Han; Yinying Jiang; Weiwei Zhu; Yucheng Liu (Journal of Hazardous Materials, 2026)

Unveiling the metabolic mechanism of pesticide in food fermentation through metagenomics and metabolomics: A case study of β-cypermethrin in Pixian broad-bean paste - Siqi Huang; Xuan Yu; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (Food Chemistry, 2026)

Intelligent non-invasive testing of food quality: Advancing accuracy and efficiency powered by artificial intelligence - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Trends in Food Science & Technology, 2025)

Macrobenthos communities and ecological quality assessment in the subtropical estuary: Insights for management of marine protected area - Jian-Yu Dong; Kunlong Qiu; Hongbin Zeng; Gorka Bidegain; Gang Hou; Ning Chen; Xuefeng Wang (Regional Studies in Marine Science, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Removal of Sb(V) from textile wastewater with iron-based coagulants: Influence factors, precipitate speciation and mechanism analysis - Xingtao Xue; Min Yao; Junxin Yu; Huiyun Lu; Yubo Liu; Hongbin Wang; Huasheng Gao (Journal of Water Process Engineering, 2025)

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Meta-terahertz sensing: Metamaterial-enhanced rapid and efficient detection of food contaminants - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Chemical Engineering Journal, 2025)

Enhancing food safety and quality: multiplex detection using smart nanostructured molecular logic technologies - Xinru Yu; Hongbin Pu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Fast real-time monitor of rice grains infested with Sitophilus oryzae based on terahertz imaging combined with machine learning - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Food Control, 2025)

Enhancing alkaline protease production in Bacillus amyloliquefaciens via surfactin-mediated mechanisms and metabolic engineering - Fang Zeng; Yujuan Liu; Dunzhi Liu; Yuqiang Li; Weizhou Xu; Yu Li; Huitu Zhang; Yihan Liu; Hongbin Wang; Fuping Lu (Bioresource Technology, 2025)

Urban underground space value assessment and regeneration strategies in symbiosis with the urban block: A case study of large residential areas in Beijing - Hongbin Yu; Zhilong Chen; Wanjie Hu; Jian Zhang; Chongyuan Xu; Bin Hu (Tunnelling and Underground Space Technology, 2025)

Post-synthetic modification and application of sulfhydryl-functionalized carbon quantum dots for label-free Ag+ detection - Yanzhi He; Pengyuan Yin; Xiaopei Li; Jinghang Li; Jie Ma; Hang Yu; Wenrong Yang; Lijun Luo; Wei Tan; Hongbin Wang (Process Safety and Environmental Protection, 2025)

Machine learning assisted nanozyme sensor array for accurate identification and discrimination of flavonoids in healthy tea - Zemin Ren; Qingxu Deng; Yu Wang; Yajun Yang; Hongbin Wang; Fufeng Liu; Wenjie Jing (Food Chemistry, 2025)

Dual-band terahertz metamaterial sensor integrated with deep learning for synergistic identification of red wine varieties - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Chemical Engineering Journal, 2025)

Compositional and functional succession of soil bacterial communities during long-term rice cultivation on saline-alkali soils: Insights derived from a new perspective on core bacterial taxa - Yu SUN; Li JI; Jingjing CHANG; Yingxin LI; Hongbin WANG; Deliang LU; Chunjie TIAN (Pedosphere, 2025)

LC-MS/MS-based metabolomic of pink Auricularia cornea grown on Lycium barbarum sawdust substrate - Lei Ye; Xuezhen Yang; Zhenzhu Huang; Bo Zhang; Qing Tian; Yu Huang; Wei Tan; Mingjun Feng; Xiaolin Li; Hongbin Xu (Food Chemistry, 2025)

Adolescent marginal zinc deficiency upregulated BDNF and TrkB expression, impaired hippocampal and cortical development, and induced abnormal behaviors in male mice - Rou Li; Qiwei Dai; Tian Yu; Yajing Sun; Yanxia Li; Tianyang Zhao; Hongbin Xu; Liang Wang; Yuxiang Wang; Xia Gao; Xiaozhi Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Terracing stabilizes and enhances soil organic carbon sequestration benefits of revegetation on the Loess Plateau, China - Hui Cheng; Hao Feng; Xiaoping Zhang; Zhiguang Li; Kaiyang Yu; Hongbin Ma; Jia Xu (CATENA, 2025)

Two nuclear loci Rf-m1 and Rf-m2 interplay to determine the fertility restoring efficacy of ZD-type CMS soybean - Xiaoxia Yu; Yupeng Feng; Lulu Zhou; Hongye Gao; Hongbin Wang; Yaru Chen; Jiamai Liang; Tianyu Meng; Meng Li; Yihan Yuan; Junping Yu; Hao Liu; et al. (Theoretical and Applied Genetics, 2025)

Multi-factor interaction perspective: machine learning-based analysis of Ni2⁺ adsorption onto soil - Yingdong Wu; Jiang Yu; Zixin Zeng; Zhi Huang; HongBin Jiang; Pu Wang; Siwei Deng; Lei Han; Xinyue Huangpeng; Yinying Jiang; Weiwei Zhu (Environmental Geochemistry and Health, 2025)

Assessment of metals pollution in seawater and sediment from the western Xuwen offshore area, Leizhou Peninsula, China - Hongbin Zeng; Xiaolong Shen; Jian-Yu Dong; Gorka Bidegain; Xuefeng Wang (Marine Pollution Bulletin, 2025)

Freezing-Induced Redistribution of Fe(II) Species within Clay Minerals for Nonlinear Variations in Hydroxyl Radical Yield and Contaminant Degradation - Dong Yu; Hongbin Peng; Chenglong Yu; Wenwen Ji; Xin Wang; Shengyan Pu (Journal of Earth Science, 2025)

Loading palladium clusters in porous organic cages for simultaneously enhancing H2 permeability and H2/CH4 selectivity of molecularly mixed composite membranes - Jia Pang; Haoyu Xu; Lu Qiao; Yao Wang; Liting Yu; Hongbin Wang; Caiyan Zhang; Hu Chang; Lili Fan; Rongming Wang; Zixi Kang; Daofeng Sun (Chemical Engineering Journal, 2025)

Developments in food neonicotinoids detection: novel recognition strategies, advanced chemical sensing techniques, and recent applications - Xinru Yu; Hongbin Pu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Compression-shear capacity of circumferential joint with dowel in shield tunnel: From experiments to analytical solution - Junchen Zhang; Qixiang Yan; Yu Zhao; Minghui Sun; Chaofan Yao; Hongbin Xu (Tunnelling and Underground Space Technology, 2025)

In vitro simulated digestive properties of Monascus vinegar melanoidins, and cytoprotective functions on Caco-2 cells - Kuaitian Wang; Yuwei Li; Xiaojia Bian; Chen Wang; Donghui Geng; Linwei Yu; Yongqiang Cheng; Hongbin Chen; Ning Tang (Food Research International, 2025)

Synergistic evolution of hydrological and movement characteristics of Majiagou landslide and identification of key triggering factors through interpretable machine learning - Wenmin Yao; Xin Zhang; Changdong Li; Yiming Lv; Yu Fu; Robert E. Criss; Hongbin Zhan; Changbin Yan (Bulletin of Engineering Geology and the Environment, 2025)

An advanced deep learning-driven Terahertz metamaterial sensor for distinguishing different red wines - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Chemical Engineering Journal, 2025)

Sediment oxygen uptake and hypoxia in coastal oceans, the Pearl River Estuary region - Jing Sun; Liuqian Yu; Xingyu Yang; Jianping Gan; Hongbin Yin; Jiying Li (Water Research, 2024)

Interface phonon scattering suppression boosts heat conduction in thermal interface materials - Zhiqiang Chen; Cuiqian Yu; Ying Ge; Kaiqin Ou; Jie Chen; Hongbin Lu (Chemical Engineering Journal, 2024)

Application of metal-organic frameworks for photocatalytic degradation of microplastics: Design, challenges, and scope - Minse Kim; Yu-Rim Ahn; Soyeong Yoon; Jaewon Choi; Hongbin Kim; Kwang Suk Lim; Suk-Jin Ha; Jeong-Ann Park; Hyun-Ouk Kim (Chemosphere, 2024)

In situ enhanced chlorine oxide radical generation on a novel space-confined photoanode and its application for ammonia oxidation: Structure, performance, and mechanism - Ting Su; Yunhe Gong; Xue Cui; Xinhong Wang; Yanan Zhang; Hongbin Yu (Chemical Engineering Journal, 2024)

A novel neuroprotective method against ischemic stroke by accelerating the drainage of brain interstitial fluid - Jingge Lian; Liu Yang; Hanbo Tan; Shaoyi Su; Leonor Serrano Lopes; Fangxiao Cheng; Junhao Yan; Yu Fu; Wanyi Fu; Zhaoheng Xie; Jianfei Sun; Jicong Zhang; et al. (Science China Life Sciences, 2024)

A ratiometric fluorescence probe based on the N, S co-doped dots and silver nanoclusters for the sensitive detection of Hg2+ - Pengyuan Yin; Shaoqing Li; Yanzhi He; Guixiang Yao; Hang Yu; Wenrong Yang; Hongbin Wang; Wei Tan (Process Safety and Environmental Protection, 2024)

Amorphous bimetallic-organic framework enable accelerated redox kinetics and polysulfide trapping for lithium-sulfur batteries - Jingkun Bi; Lu Chen; Xiao Yan; Jian Guo; Ya Tang; Ma Jian; Shuo Meng; Kexuan Liao; Jia Yu; Wenli Yao; Ting He; Hongbin Zhao (Chemical Engineering Journal, 2024)

Development of preferred sizes for building-integrated lighting units (BILUs) - Peng Chen; Juan Yu; Yuting Wu; Lixiong Wang; Hongbin Guo; Yuanye He (Building and Environment, 2024)

Microwave-assisted preparation of yellow fluorescent graphitic carbon nitride quantum dots for trace tetracycline-specific detection - Yanzhi He; Xiaopei Li; Guixiang Yao; Shuju Fang; Hang Yu; Tianru Zou; Wei Tan; Hongbin Wang (Chemosphere, 2024)

Mechanisms of enhancing MgO for stabilization/solidification of Pb-contaminated red clay through CO2 sequestration - Rulong Ban; Fusheng Zha; Bo Kang; Shan Wu; Yu Song; Hongbin Chen (Journal of Environmental Management, 2024)

Interaction of pepper numbing substances with myofibrillar proteins and numbness perception under thermal conditions: A structural mechanism analysis - Shuaiqian Wang; Yu Chen; Yan Lu; Diandian Jiang; Hongbin Lin; Zhenju Jiang; Jie Tang; Wei Dong; Jie Zhao (Food Chemistry, 2024)

Elevated temperature magnifies the acute and chronic toxicity of clothianidin to Eisenia fetida - Yingnan Wang; Jiatao Shen; Hongbin Lang; Fan Shen; Luqing Zhang; Hua Fang; Yunlong Yu (Environmental Pollution, 2024)

Pyrite geochemical fingerprinting on skarn ore-forming processes: A case study from the Huangshaping W–Sn–Cu–Pb–Zn deposit in the Nanling Range, South China - Lianjie Zhao; Yongjun Shao; Yu Zhang; Liangyu Liu; Shitao Zhang; Hongtao Zhao; Hongbin Li (Journal of Geochemical Exploration, 2024)

Ultra-trace Ag doped carbon quantum dots with peroxidase-like activity for the colorimetric detection of glucose - Wei Tan; Guixiang Yao; Hang Yu; Yanzhi He; Mingrong Lu; Tianru Zou; Xiaopei Li; Pengyuan Yin; Pei Na; Wenrong Yang; Min Yang; Hongbin Wang (Food Chemistry, 2024)

Enhanced electrocatalytic reduction of nitrate over a ternary alloy catalyst of CuPdFe: Structure, performance, and mechanism - Yuchun Feng; Ting Su; Yunhe Gong; Hongbin Yu; Weichao Qin; Mingxin Huo (Journal of Environmental Chemical Engineering, 2024)

Enhanced treatment of reverse osmosis concentrates by ozone micro-nano bubbles coupled with catalytic ceramic membranes - Shuang Wang; Jiakai Qiu; Mingzhu Ren; Yu Cui; Yongbing Xie; Hongbin Cao (Journal of Water Process Engineering, 2024)

Detoxification of copper and zinc from anaerobic digestate effluent by indigenous bacteria: Mechanisms, pathways and metagenomic analysis - Hongbin Yan; Zhiqiang Gu; Qi Zhang; Yunpu Wang; Xian Cui; Yuhuan Liu; Zhigang Yu; Roger Ruan (Journal of Hazardous Materials, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

Photoperiod associated late flowering reaction norm: Dissecting loci and genomic-enviromic associated prediction in maize - Alper Adak; Seth C. Murray; José I. Varela; Valentina Infante; Jennifer Wilker; Claudia Irene Calderón; Nithya Subramanian; Natalia de Leon; Jianming Yu; Matthew A. Stull; Marcel Brun; Joshua Hill; et al. (Field Crops Research, 2024)

Controls on Deep and Shallow Gas Hydrate Reservoirs in the Dongsha Area, South China Sea: Evidence from Sediment Properties - Chenyang Bai; Hongbin Wang; Qing Li; Yu Zhang; Xiaolei Xu (Journal of Marine Science and Engineering, 2024)
The Dongsha area, a key region in the northern South China Sea (SCS), features both diffusive deep and seepage shallow gas hydrate reservoirs. Utilizing sediment samples from gas hydrate reservoirs and adjacent layers at sites W08 and W16 in the Dongsha area, this study aims to uncover the sediment property differences between deep and shallow gas hydrate reservoirs and their impact on gas hydrate accumulation through grain size, X-ray diffraction, and specific surface area (SSA) analyses. The findings classify the study intervals into four distinct layers: shallow non-gas hydrate layer (shallow-NGHL), shallow gas hydrate reservoir (shallow-GHR), deep non-gas hydrate layer (deep-NGHL), and deep gas hydrate reservoir (deep-GHR). In the clayey silt sediment reservoirs, grain size has a minor influence on gas hydrate reservoirs. Both shallow and deep NGHLs, characterized by high smectite content and SSA, possess a complex structure that impedes gas and fluid migration and offers limited potential reservoir space. Consequently, both shallow and deep NGHLs function as sealing beds. The deep GHR, having low smectite content and SSA, exhibits a strong capacity for gas and fluid migration and greater potential reservoir space. As a result, sediment properties significantly influence the deep GHR. Seepage primarily controls the shallow GHR.

A TiO2 nanotube photoanode (blue TiO2 nanotube/RuO2/BiVO4) for efficient acetaminophen degradation and nitrogen removal - Xiaolin Sun; Ting Su; Xue Cui; Hongbin Yu; Ying Lu; Weichao Qin; Mingxin Huo (Journal of Water Process Engineering, 2024)

Elimination of copper obstacle factor in anaerobic digestion effluent for value-added utilization: Performance and resistance mechanisms of indigenous bacterial consortium - Zhiqiang Gu; Hongbin Yan; Qi Zhang; Yunpu Wang; Cuixia Liu; Xian Cui; Yuhuan Liu; Zhigang Yu; Xiaodan Wu; Roger Ruan (Water Research, 2024)

Mineral dust optical properties for remote sensing and global modeling: A review - Patricia Castellanos; Peter Colarco; W. Reed Espinosa; Scott D. Guzewich; Robert C. Levy; Ron L. Miller; Mian Chin; Ralph A. Kahn; Osku Kemppinen; Hans Moosmüller; Edward P. Nowottnick; Adriana Rocha-Lima; et al. (Remote Sensing of Environment, 2024)

Application of Italian ryegrass residue changes the soil biochemical properties and bacterial communities in Southern China - Yao Xiang; Mengyan Cao; Hongbin He; Yu Song; Cheng Jin; Guorong Xin; Chuntao He (Applied Soil Ecology, 2024)

Elevating sensing capability via dual-atom catalysts boosted luminol cathodic electrochemiluminescence - Yan-Chen Kong; Dan-Ling Wang; Jing-Jing Zhang; Yu-Xin Yang; Cong-Hui Xu; Rida Javed; Hongbin Zhao; Daixin Ye; Wei Zhao (Analytica Chimica Acta, 2024)

Micro(nano)plastics in food system: potential health impacts on human intestinal system - Siyue Wen; Yu Zhao; Mengqi Wang; Hongbin Yuan; Hengyi Xu (Critical Reviews in Food Science and Nutrition, 2024)

Recent progress of particle electrode materials in three-dimensional electrode reactor: synthesis strategy and electrocatalytic applications - Siwen Li; Bo Jiang; Gen Liu; Chunyan Shi; Hongbin Yu; Yingzi Lin (Environmental Science and Pollution Research, 2024)

Aerosol optical and radiative properties and their environmental effects in China: A review - Huizheng Che; Xiangao Xia; Hujia Zhao; Lei Li; Ke Gui; Yu Zheng; Jingjing Song; Bing Qi; Jun Zhu; Yucong Miao; Yaqiang Wang; Zhili Wang; et al. (Earth-Science Reviews, 2024)

Italian ryegrass (Lolium multiflorum L.)-rice (Oryza sativa L.) rotation promotes the nitrogen cycle in the rice rhizosphere through dominant ammonia-oxidizing bacteria - Mengyan Cao; Yao Xiang; Hongbin He; Junkang Cheng; Yu Song; Cheng Jin; Guorong Xin; Chuntao He (Applied Soil Ecology, 2024)

Higher temperature and daily fluctuations aggravate clothianidin toxicity towards Limnodrilus hoffmeisteri - Yingnan Wang; Jiatao Shen; Xin Li; Hongbin Lang; Luqing Zhang; Hua Fang; Yunlong Yu (Science of The Total Environment, 2023)

Long-term variations of water quality and nutrient load inputs in a large shallow lake of Yellow River Basin: Implications for lake water quality improvements - Shengyue Yu; Xinzhong Du; Qiuliang Lei; Xue Wang; Shengcai Wu; Hongbin Liu (Science of The Total Environment, 2023)

Nano light conversion agents: recent advances, future prospects and challenges in enhancing plant green cultivation - Xinru Yu; Hongbin Pu; Da-Wen Sun (Journal of Cleaner Production, 2023)

Iron bound phosphorus predominates the contribution of phosphorus to lake system from terrigenous source: The evidence from the small watershed scale - Hezhong Yuan; Haixiang Wang; Yiwei Cai; Hongbin Yin; Qingfei Zeng; Enfeng Liu; Qiang Li; Yu Wang (Water Research, 2023)

Northern high-latitude sea ice variation linked with East Asian monsoon anomalies during the Younger Dryas - Xiaolong Chen; Hongbin Zhang; Michael L. Griffiths; Xiaogui Peng; Liangzhe Yang; Ming Yu; Junhua Huang; Shuyu Xue; Hai Cheng; Shuai Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Rice straw as microalgal biofilm bio-carrier: Effects of indigenous microorganisms on rice straw and microalgal biomass production - Hongbin Yan; Qi Zhang; Yunpu Wang; Xian Cui; Yuhuan Liu; Zhigang Yu; Shuming Xu; Roger Ruan (Journal of Environmental Management, 2023)

Feature construction methods for processing and analysing spectral images and their applications in food quality inspection - Hongbin Pu; Jingxiao Yu; Da-Wen Sun; Qingyi Wei; Zhe Wang (Trends in Food Science & Technology, 2023)

Supramolecular nanoassemblies-mediated GSH depletion boosts synergistic chemo- and photodynamic therapy for immunogenicity enhancement - Dun Wang; Wei Ma; Yun Huang; Wei Wang; Shuang Li; Hongbin Liu; Yuqi Zhao; Dongdong Peng; Cui-Yun Yu; Hua Wei (Chemical Engineering Journal, 2023)

A temporally relaxed theory of physically or chemically non-equilibrium solute transport in heterogeneous porous media - Ying-Fan Lin; Junqi Huang; Elliot J. Carr; Tung-Chou Hsieh; Hongbin Zhan; Hwa-Lung Yu (Journal of Hydrology, 2023)

Interpenetrating network expansion sponge based on chitosan and plasma for ultrafast hemostasis of arterial bleeding wounds - Yuting Shi; Wenwen Yu; Xiaoqin Liang; Ju Cheng; Yufei Cao; Mingsheng Liu; Yu Fang; Zheng Yang; Hongbin Liu; Hua Wei; Guanghui Zhao (Carbohydrate Polymers, 2023)

Comparative review on microbial electrochemical technologies for resource recovery from wastewater towards circular economy and carbon neutrality - Shihai Deng; Chaoqi Wang; Huu Hao Ngo; Wenshan Guo; Na You; Hao Tang; Hongbin Yu; Long Tang; Jie Han (Bioresource Technology, 2023)

Single-atom boosted electrochemiluminescence via phosphorus doping of Fe–N/P–C catalysts - Yu-Xin Yang; Qian-Nan He; Cong-Hui Xu; Rida Javed; Hongbin Zhao; Daixin Ye; Wei Zhao (Analytica Chimica Acta, 2023)

Controlling internal nitrogen and phosphorus loading using Ca-poor soil capping in shallow eutrophic lakes: Long-term effects and mechanisms - Chuanzhe Sun; Jicheng Zhong; Gang Pan; Robert J.G. Mortimer; Juhua Yu; Shuailong Wen; Lei Zhang; Hongbin Yin; Chengxin Fan (Water Research, 2023)

Study on the mechanism of an enteromorpha-based compound inhibitor for inhibiting the spontaneous combustion of coal using in situ infrared spectroscopy and thermal analysis kinetics - Hao Dong; Xiangming Hu; Anqi Yu; Wei Wang; Qiankun Zhao; Hongbin Wei; Zhenyu Yang; Xuwei Wang; Chongyang Luo (Journal of Environmental Chemical Engineering, 2023)

Sulfamethazine degradation by sulfite through GAC@Ni/Fe Three-Dimensional (3D) particle electrode activation: Contribution of active substance and synergy - Siwen Li; Hongbin Yu; Yingzi Lin; Suiyi Zhu; Gen Liu; Chunyan Shi (Process Safety and Environmental Protection, 2023)

A novel (Zr/Ce)UiO-66(NH2)@g-C3N4 Z-scheme heterojunction for boosted tetracycline photodegradation via effective electron transfer - Susu Ren; Jiahuan Dong; Xinyu Duan; Tingting Cao; Hongbin Yu; Ying Lu; Dandan Zhou (Chemical Engineering Journal, 2023)

Reconfigurable origami-inspired window for tunable noise reduction and air ventilation - Xiaomeng Jin; Hongbin Fang; Xiang Yu; Jian Xu; Li Cheng (Building and Environment, 2023)

Rapid detection of neutralising acid adulterants in raw milk using a milk component analyser and chemometrics - Huaixiang Tian; Bin Chen; Hongbin Yu; Xinman Lou; Yong Li; Haiyan Yu; Liqiong Chen; Chen Chen (Food Additives & Contaminants: Part A, 2022)

The boosting of microwave roasting technology on the desulfurization of phosphate rock - Di He; Mei Yao; Hongbin Wang; Binghua Xie; Qian Yu; Na Geng; Lijuan Jia (Environmental Science and Pollution Research, 2022)

AFAP1-AS1: a rising star among oncogenic long non-coding RNAs - Fang Xiong; Kunjie Zhu; Su Deng; Hongbin Huang; Liting Yang; Zhaojian Gong; Lei Shi; Yi He; Yanyan Tang; Qianjin Liao; Jianjun Yu; Xiaoling Li; et al. (Science China Life Sciences, 2021)

Comparative transcriptomic analysis of the brain in Takifugu rubripes shows its tolerance to acute hypoxia - Mingxiu Bao; Fengqin Shang; Fujun Liu; Ziwen Hu; Shengnan Wang; Xiao Yang; Yundeng Yu; Hongbin Zhang; Chihang Jiang; Jielan Jiang; Yang Liu; Xiuli Wang (Fish Physiology and Biochemistry, 2021)

Distribution and Activity of Ammonia-Oxidizers on the Size-Fractionated Particles in the Pearl River Estuary - Li Ma; Shangjin Tan; Hongbin Liu; Shuh-Ji Kao; Minhan Dai; Jin-Yu Terence Yang (Frontiers in Marine Science, 2021)
To distinguish between the distribution and activity of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) in the Pearl River estuary (PRE), we investigated the DNA- and cDNA-based β-proteobacterial and archaeal amo A genes on three size-fractionated particles of >3.0 μm, 0.45–3.0 μm, and 0.22–0.45 μm. Results showed that AOB were more abundant in the freshwater with high concentrations of ammonium (NH 4 + ) and low dissolved oxygen, whereas AOA were dominant in the NH 4 + -depleted seawater and sensitive to temperature. Obvious shifts in ammonia-oxidizing communities were found along the salinity gradient in the PRE. AOB clearly presented a particle-associated nature, as evidenced by higher relative abundance of amo A genes attached to the large particles (>3.0 μm) and their transcripts exclusively detected on this fraction. Moreover, higher transcriptional activity (indicated by the cDNA/DNA ratio) of AOB on the large particles, suggesting AOB were actively involved in ammonia oxidation despite their lower abundance in the mid- and lower estuarine regions. In contrast, AOA exhibited higher transcriptional activity on the 0.45–3.0 μm and 0.22–0.45 μm particles, implying the free-living strategy of these microbes. Together, these findings from field observations provide useful information on the ecological strategies of ammonia-oxidizing communities in response to different environmental conditions.

Synthesis of novel erdite nanorods for the activation of peroxymonosulfate during p-nitrophenol wastewater treatment - Tong Sun; Yu Chen; Suiyi Zhu; Zhihua Wang; Jiancong Liu; Xinfeng Xie; Hongbin Yu (Environmental Science and Pollution Research, 2021)

Screening maize (Zea mays L.) varieties with low accumulation of cadmium, arsenic, and lead in edible parts but high accumulation in other parts: a field plot experiment - Ningke Yang; Hongbin Wang; Haijuan Wang; Zhongzhen Wang; Jiakang Ran; Siyu Guo; Yu Peng (Environmental Science and Pollution Research, 2021)

IAP’s Solar-Powered Unmanned Surface Vehicle Actively Passes through the Center of typhoon Sinlaku (2020) - Hongbin Chen; Jun Li; Wenying He; Shuqing Ma; Yingzhi Wei; Jidong Pan; Yu Zhao; Xuefen Zhang; Shuzhen Hu (Advances in Atmospheric Sciences, 2021)

Expression of P2X receptors in the rat anterior pituitary - Wenqi Zhao; Yu Zhang; Ruihua Ji; Gillian E. Knight; Geoffrey Burnstock; Hongbin Yuan; Zhenghua Xiang (Purinergic Signalling, 2020)

Modeling study of the impact of complex terrain on the surface energy and hydrology over the Tibetan Plateau - Xuehua Fan; Yu Gu; Kuo-Nan Liou; Wei-Liang Lee; Bin Zhao; Hongbin Chen; Daren Lu (Climate Dynamics, 2019)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Host–Symbiont Interactions in Deep-Sea Chemosymbiotic Vesicomyid Clams: Insights From Transcriptome Sequencing - Yi Lan; Jin Sun; Weipeng Zhang; Ting Xu; Yu Zhang; Chong Chen; Dong Feng; Hongbin Wang; Jun Tao; Jian-Wen Qiu; Pei-Yuan Qian (Frontiers in Marine Science, 2019)

Toll-Like Receptor 4 Promotes Th17 Lymphocyte Infiltration Via CCL25/CCR9 in Pathogenesis of Experimental Autoimmune Encephalomyelitis - Ying Zhang; Jingjing Han; Meili Wu; Lu Xu; Yu Wang; Wen Yuan; Fang Hua; Hongbin Fan; Fuxing Dong; Xuebin Qu; Ruiqin Yao (Journal of Neuroimmune Pharmacology, 2019)

PB2 and hemagglutinin mutations confer a virulent phenotype on an H1N2 avian influenza virus in mice - Zhijun Yu; Zhiguang Ren; Yongkun Zhao; Kaihui Cheng; Weiyang Sun; Xinghai Zhang; Jiaqiang Wu; Hongbin He; Xianzhu Xia; Yuwei Gao (Archives of Virology, 2019)

Continuous efficient removal and inactivation mechanism of E. coli by bismuth-doped SnO2/C electrocatalytic membrane - Pengfei Wang; Yu Deng; Limei Hao; Lei Zhao; Xinqi Zhang; Cheng Deng; Hongbin Liu; Mengfu Zhu (Environmental Science and Pollution Research, 2019)

Science questions and knowledge gaps to study microbial transport and survival in Asian and African dust plumes reaching North America - Andrew C. Schuerger; David J. Smith; Dale W. Griffin; Daniel A. Jaffe; Boris Wawrik; Susannah M. Burrows; Brent C. Christner; Cristina Gonzalez-Martin; Erin K. Lipp; David G. Schmale III; Hongbin Yu (Aerobiologia, 2018)

Photochemical oxidation of di-n-butyl phthalate in atmospheric hydrometeors by hydroxyl radicals from nitrous acid - Yu Lei; Chengzhu Zhu; Jun Lu; Yongchao Zhu; Qiuyue Zhang; Tianhu Chen; Hongbin Xiong (Environmental Science and Pollution Research, 2018)

The influence of large-scale climate phenomena on precipitation in the Ordos Basin, China - Yu Zhong; Liyuan Lei; Youcun Liu; Yonghong Hao; Chris Zou; Hongbin Zhan (Theoretical and Applied Climatology, 2017)

Community patterns and temporal variation of picoeukaryotes in response to changes in the Yellow Sea Warm Current - Zhimeng Xu; Xue Song; Min Wang; Qian Liu; Yong Jiang; Hongbing Shao; Hongbin Liu; Kunpeng Shi; Yang Yu (Journal of Oceanography, 2017)

Heat Acclimation of Bifidobacterium longum and Proteomic Changes Behind It - Hongbin Wang; Yu Li; Yong Zhang; Qinglong Xi; Yueting Cao; Fuping Lu (Probiotics and Antimicrobial Proteins, 2017)

Comparison of Aerosol Optical Properties Between Two Nearby Urban Sites in Beijing, China - Jie Yu; Huizheng Che; Quanliang Chen; Hongbin Chen; Philippe Goloub; Ke Gui; Yu Zheng; Hong Wang; Yaqiang Wang; Linchang An; Tianze Sun; Xiaoye Zhang; et al. (Aerosol Science and Engineering, 2017)

Improving matching ability of descriptors on multi-sensor images with complementary information - Yong Li; Hang Yu; Fang Chen; Hongbin Jin (Arabian Journal of Geosciences, 2016)

AtFes1A is essential for highly efficient molecular chaperone function in Arabidopsis - Can Fu; Jingxia Zhang; Xiaxia Liu; Wenwen Yang; Hongbin Yu; Jian Liu (Journal of Plant Biology, 2015)

Experimental infection of dogs with H6N1 avian influenza A virus - Kaihui Cheng; Zhijun Yu; Yuwei Gao; Xianzhu Xia; Hongbin He; Yuping Hua; Hongliang Chai (Archives of Virology, 2014)

Impacts of intercontinental transport of anthropogenic fine particulate matter on human mortality - Susan C. Anenberg; J. Jason West; Hongbin Yu; Mian Chin; Michael Schulz; Dan Bergmann; Isabelle Bey; Huisheng Bian; Thomas Diehl; Arlene Fiore; Peter Hess; Elina Marmer; et al. (Air Quality, Atmosphere & Health, 2014)

Block of P2X7 receptors could partly reverse the delayed neuronal death in area CA1 of the hippocampus after transient global cerebral ischemia - Qiang Yu; Zhili Guo; Xiaofeng Liu; Qing Ouyang; Cheng He; Geoffrey Burnstock; Hongbin Yuan; Zhenghua Xiang (Purinergic Signalling, 2013)

Surveillance and molecular characterization of Newcastle disease virus in seafowl from coastal areas of China in 2011 - Xiaoyuan Yuan; Youling Wang; Jun Li; Kexiang Yu; Jinxing Yang; Huaiying Xu; Yuxia Zhang; Hongbin Ai; Jinbao Wang (Virus Genes, 2013)

An in vivo study with an MRI tracer method reveals the biophysical properties of interstitial fluid in the rat brain - HongBin Han; Kai Li; JunHao Yan; Kai Zhu; Yu Fu (Science China Life Sciences, 2012)

Characterization of microRNAs from sheep (Ovis aries) using computational and experimental analyses - Xihui Sheng; Xuemei Song; Yan Yu; Lili Niu; Shangang Li; Hongbin Li; Caihong Wei; Tao Liu; Li Zhang; Lixin Du (Molecular Biology Reports, 2011)

Synthesis of GDP-mannose using coupling fermentation of recombinant Escherichia coli - Jia Honghong; Lu Fuping; Li Yu; Liu Xiaoguang; Liu Yihan; Wang Hongbin; Li Jing; Cao Yueting (Biotechnology Letters, 2011)

Optimized procedure for expression and renaturation of recombinant human bone morphogenetic protein-2 at high protein concentrations - Hongbin Zhang; Jie Wu; Yu Zhang; Na Fu; Jie Wang; Shujin Zhao (Molecular Biology Reports, 2010)

Novel microRNAs in silkworm (Bombyx mori) - Yimei Cai; Xiaomin Yu; Qing Zhou; Caixia Yu; Haiyan Hu; Jiucheng Liu; Hongbin Lin; Jin Yang; Bing Zhang; Peng Cui; Songnian Hu; Jun Yu (Functional & Integrative Genomics, 2010)

Significant variations of surface albedo during a snowy period at Xianghe observatory, China - Yu Yu; Hongbin Chen; Xiangao Xia; Yuejian Xuan; Ke Yu (Advances in Atmospheric Sciences, 2010)

Mid-Holocene climate variations recorded by palaeolake in marginal area of East Asian Monsoon: A multi-proxy study - Hao Long; Hongbin Tan; Naiang Wang; Liangcheng Tan; Yu Li (Chinese Geographical Science, 2007)

Molecular Evidence for Asymmetric Evolution of Sister Duplicated Blocks after Cereal Polyploidy - Hongbin Wang; Lujun Yu; Fei Lai; Liangshi Liu; Jinfa Wang (Plant Molecular Biology, 2005)

Study on the thermal internal boundary layer and dispersion of air pollutant in coastal area by numerical simulation - Jiang Weimei; Yu Hongbin (Advances in Atmospheric Sciences, 1994)